Auditory Information Accelerates the Visuomotor Reaction Speed of Elite Badminton Players in Multisensory Environments - Hülsdünker, Thorben; Riedel, David; Käsbauer, Hannes; Ruhnow, Diemo; Mierau, Andreas (Frontiers in Human Neuroscience, 2021)
Although vision is the dominating sensory system in sports, many situations require multisensory integration. Faster processing of auditory information in the brain may facilitate time-critical abilities such as reaction speed however previous research was limited by generic auditory and visual stimuli that did not consider audio-visual characteristics in ecologically valid environments. This study investigated the reaction speed in response to sport-specific monosensory (visual and auditory) and multisensory (audio-visual) stimulation. Neurophysiological analyses identified the neural processes contributing to differences in reaction speed. 19 elite badminton players participated in this study. In a first experiment, the sound profile and shuttle speed of smash and drop strokes were identified on a badminton court using high-speed video cameras and binaural recordings. The speed and sound characteristics were transferred into auditory and visual stimuli and presented in a lab-based experiment, where participants reacted in response to sport-specific monosensory or multisensory stimulation. Auditory signal presentation was delayed by 26 ms to account for realistic audio-visual signal interaction on the court. N1 and N2 event-related potentials as indicators of auditory and visual information perception/processing, respectively were identified using a 64-channel EEG. Despite the 26 ms delay, auditory reactions where significantly faster than visual reactions (236.6 ms vs. 287.7 ms, p<0.001) but still slower when compared to multisensory stimulation (224.4 ms, p=0.002). Across conditions response times to smashes were faster when compared to drops (233.2 ms, 265.9 ms, p<0.001). Faster reactions were paralleled by a lower latency and higher amplitude of the auditory N1 and visual N2 potentials. The results emphasize the potential of auditory information to accelerate the reaction time in sport-specific multisensory situations. This highlights auditory processes as a promising target for training interventions in racquet sports.